SYNTHESIS OF NEW SPIROHETERYL-SUBSTITUTED BUTANOLIDES (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
On the base of 2-etoxycarbonil-2-brom-4-alkoxymethylbutanolides were synthesized new derivatives of spiroheterylcombinationes butanolides.
Keywords: 2-etoxycarbonil-2-brom-4-alkoxymethylbutanolides; new derivatives